Technological aprobation of integral cluster setup for complex compound composites syntesis - Yakovin, S.; Dudin, S.; Zykov, A.; Shyshkov, A.; Farenik, V. (Вопросы атомной науки и техники, 2012)
In the present paper the results of technological approbation of the integral cluster set-up for synthesis of various types of high-quality coatings such as Al₂O₃, TiO₂, ZrO₂, AlN, TiN, and others with coating thickness up to 10 mkm are presented. Сurrent-voltage characteristics of magnetron discharge in argon mixtures with oxygen and nitrogen for various gas pressures and for various target materials have been measured. Представлены результаты технологической апробации интегральной кластерной установки для синтеза высококачественных покрытий типа Al₂O₃, TiO₂, ZrO₂, AlN, TiN и других, толщиной до 10 мкм. Были измерены вольт-амперные характеристики магнетронного разряда в смесях аргона с кислородом и азотом, при различных давлениях рабочего газа и разных материалах мишени. Представлено результати технологічної апробації інтегральної кластерноїї установки для синтезу високоякісних покриттів типу Al₂O₃, TiO₂, ZrO₂, AlN, TiN та інших, товщиною до 10 мкм. Було виміряно вольт-амперні характеристики магнетронного розряду в сумішах аргону з киснем та азотом, при різних тисках робочого газу та різних матеріалах мішені.